2013
DOI: 10.5665/sleep.2796
|View full text |Cite
|
Sign up to set email alerts
|

Brain Gray Matter Deficits in Patients with Chronic Primary Insomnia

Abstract: Joo EY; Noh HJ; Kim JS; Koo DL; Kim D; Hwang KJ; Kim JY; Kim ST; Kim MR; Hong SB. Brain gray matter deficits in patients with chronic primary insomnia. 2013;36(7):999-1007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
184
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(208 citation statements)
references
References 43 publications
21
184
3
Order By: Relevance
“…48 Joo et al found that the PCPIs showed significant reduction of gray matter concentrations in the dorsolateral prefrontal cortices compared with the GSs. 7 Our previous study also found the PCPI-Ms showed lower regional homogeneity in the dorsolateral prefrontal cortex compared with the GS-Ms. 23 In support of these findings, in the present study we found that the PCPI-Fs showed lower ALFF in the left dorsolateral prefrontal cortex compared with the GS-Fs. These findings suggest that the attentional and cognitive dysfunction may contribute to the impaired dorsolateral prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Joo et al found that the PCPIs showed significant reduction of gray matter concentrations in the dorsolateral prefrontal cortices compared with the GSs. 7 Our previous study also found the PCPI-Ms showed lower regional homogeneity in the dorsolateral prefrontal cortex compared with the GS-Ms. 23 In support of these findings, in the present study we found that the PCPI-Fs showed lower ALFF in the left dorsolateral prefrontal cortex compared with the GS-Fs. These findings suggest that the attentional and cognitive dysfunction may contribute to the impaired dorsolateral prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…44 Joo et al found decreased volume of gray matter in the MPFC in the PCPIs compared with the GSs. 7 Altena et al found a smaller gray matter volume in the left orbitofrontal cortex in the PCPIs compared with the GSs. 45 Our previous regional homogeneity study found that both the PCPI-Fs and the PCPI-Ms showed lower regional homogeneity in the VMPFC, 23 and our previous functional connectivity study found that the PCPIs showed significant decreased functional connectivity between the MPFC and the right MTL, and between the left MTL and the left inferior parietal cortices using the seed-based region-to-region functional connectivity method.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported associations between selfreport primary insomnia and reduced cortical gray matter volume in several brain regions including the orbitofrontal cortex, 15,16 hippocampus, 17,18 and precuneus. 15 Moreover, in individuals without a clinical diagnosis of insomnia, self-report metrics of poorer sleep quality have been associated with Significance Sleep fragmentation is a common symptom in older adults and is associated with a number of adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 With respect to OSA, a variety of neuroimaging studies suggest evidence of brain neuronal loss or dysfunction. 21 Gray matter abnormalities also have been observed some, [22][23][24] but not all studies of patients with chronic insomnia. 25 Given the interconnections among TBI, OSA, insomnia, mood disturbances, cognitive decline and neurodegeneration, one can speculate that OSA and insomnia may be additional risk factors or important modifying factors for the development of CTE.…”
mentioning
confidence: 92%